2009
DOI: 10.1210/me.2008-0408
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Signaling of Estrogen to WAVE1 and Moesin Controls Neuronal Spine Formation via the Actin Cytoskeleton

Abstract: Estrogens are important regulators of neuronal cell morphology, and this is thought to be critical for gender-specific differences in brain function and dysfunction. Dendritic spine formation is dependent on actin remodeling by the WASP-family verprolin homologous (WAVE1) protein, which controls actin polymerization through the actin-related protein (Arp)-2/3 complex. Emerging evidence indicates that estrogens are effective regulators of the actin cytoskeleton in various cell types via rapid, extranuclear sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 28 publications
7
86
0
Order By: Relevance
“…kinase, thereby leading to actin polymerization and increased formation of filopodia (18,19). As calpain inhibition prevented E2-induced increase in actin polymerization, our results indicate that calpain activation is an important step leading to actin polymerization, possibly through cofilin phosphorylation/inactivation.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…kinase, thereby leading to actin polymerization and increased formation of filopodia (18,19). As calpain inhibition prevented E2-induced increase in actin polymerization, our results indicate that calpain activation is an important step leading to actin polymerization, possibly through cofilin phosphorylation/inactivation.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have shown that E2 participates in the regulation of dendritic spine morphology in area CA1 of hippocampus (18,19). E2 has been shown to inactivate cofilin by stimulating LIM 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young, cultured cortical neurons, treatment with 10 nM 17b-estradiol resulted in a rapid increase in the number of filopodia. This effect was maximal after 20 minutes of treatment but was transient because the number of filopodia returned to pretreatment levels by 60 minutes (Sanchez et al, 2009). The ability of 17b-estradiol to rapidly remodel dendritic filopodia in young, developing neurons indicates a role for estrogens in Rapid Modulation of Neuroplasticity by Brain Estrogens modulating synaptogenesis during early development of cortical circuitry.…”
Section: Rapid Regulation Of Dendritic Spines By 17b-estradiol In mentioning
confidence: 97%
“…In young developing cortical neurons, 17b-estradiol-mediated filopodia formation occurs via the activation of a c-SRC/Rac1/Cdk5/ WAVE1/Arp2/3 pathway and a RhoA/ROCK-2/moesin cascade (Sanchez et al, 2009). Although phosphorylation of WAVE1 was only achieved by 17b-estradiol and PPT, but not DPN, suggesting an ERa-dependent pathway, the direct effects of ERa activation on filopodial formation was not tested.…”
Section: B Convergent Actin Regulating Pathways Underlie Rapid Estromentioning
confidence: 99%